Pengembangan Media Pembelajaran Role-Playing untuk Meningkatkan Keterampilan Etika Komunikasi di Kalangan Siswa Kelas 8 MTS Al Azhaar Ummu Suwanah - Ahmad Reza Maulana; Muhammad Fajriansyah Solichin; Muthmainah Muthmainah; Rendy Pratama (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Communication ethics is a set of principles that regulate how to communicate politely, courteously, and effectively, which is very important in everyday life, especially in the educational environment. However, communication ethics skills are often not optimally mastered by students due to the lack of interactive and relevant learning media. This research aims to develop innovative role-playing-based learning media designed to improve the communication ethics skills of grade 8 students at MTs Al Azhaar Ummu Suwanah. This research is motivated by the importance of communication ethics skills as one of the basic competencies in learning, which is often poorly facilitated through conventional learning methods. This role-playing media is designed to provide an interactive learning experience through simulating everyday communication situations that are relevant to students' lives. Effectiveness testing was carried out through limited trials and field trials involving 8th grade students as research subjects. Data were collected through observation, and expert validation. The results showed that this role-playing learning media was effective in improving students' communication ethics skills. In addition, this media is also considered attractive, easy to use, and able to create a fun learning atmosphere. Thus, the role-playing board can be an innovative alternative to support the interaction-based learning process and direct practice in the classroom.